2006
DOI: 10.1136/bmj.332.7552.1241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telephone contact on further suicide attempts in patients discharged from an emergency department: randomised controlled study

Abstract: Objective To determine the effects over one year of contacting patients by telephone one month or three months after being discharged from an emergency department for deliberate self poisoning compared with usual treatment. Design Multicentre, randomised controlled trial. Setting 13 emergency departments in the north of France. Participants 605 people discharged from an emergency department after attempted suicide by deliberate self poisoning. Intervention The intervention consisted of contacting patients by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(202 citation statements)
references
References 17 publications
6
193
2
1
Order By: Relevance
“…Finally, this is an manageable, cost-effective and easily reproducible programme, unlike other effective programmes that are based on intensive interventions or carried out in experimental conditions (183;190). As in our study, Fleischmann et al pointed out the importance of regular contact to reduce the risk of further suicide attempt and suicide completion (183). The effectiveness of such interventions may be due to the fact that telephone management allows the listener to be aware of the needs or doubts of the patient on repeated occasions and is able to regularly assess suicidal thoughts, as well as to encourage adherence to usual treatment.…”
Section: Chapter 5 Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, this is an manageable, cost-effective and easily reproducible programme, unlike other effective programmes that are based on intensive interventions or carried out in experimental conditions (183;190). As in our study, Fleischmann et al pointed out the importance of regular contact to reduce the risk of further suicide attempt and suicide completion (183). The effectiveness of such interventions may be due to the fact that telephone management allows the listener to be aware of the needs or doubts of the patient on repeated occasions and is able to regularly assess suicidal thoughts, as well as to encourage adherence to usual treatment.…”
Section: Chapter 5 Discussionmentioning
confidence: 88%
“…Simillarly, Vaiva and colleagues observed that subjects who received telephone contact 1 month following their suicide attempts presented significantly fewer suicide attempts than those who received no contact (183). However, a subsequent interevention (telephone contact three months post attempt) did not reduce the number of subsequent suicide attempts when compared with no-contact.…”
Section: Telephone Interventions In Suicide Preventionmentioning
confidence: 97%
“…A randomized controlled study of 605 adults age 18 to 65 discharged from 13 emergency departments following a suicide attempt by drug overdose/poisoning, showed that those contacted by telephone one month after being discharged were 45% less likely to repeat a suicide attempt during the year following the index attempt than those who did not receive the telephone contact (Vaiva et al, 2007). In another study, researchers sent post cards to a group of 394 individuals randomized to the intervention group at intervals of 1, 2, 3,4,6,8,10, and 12 months after a suicide attempt.…”
Section: Alternative Prevention Approachesmentioning
confidence: 99%
“…While we agree that the evidence the editorial was based on is limited somewhat by the outcome that the studies were measuring, we feel it is important that the decisions ethics committee reach are evidence based. If the available evidence does not support an association between asking questions about suicide and suicidality, then any limitations placed on a proposed research project should be justified, particularly as the general direction of travel seems to be that asking questions is more likely to reduce suicidality than increase it (see for example: Cedereke et al 2002;Vaiva et al 2006;Biddle et al 2013). We are not saying that such a situation can never be found, but that a good case needs to be made if restrictions are put in place.…”
Section: Declaration Of Interestmentioning
confidence: 99%